Learning Innovation in Outcome Based Education: Development of Descriptive Statistics Modules for Islamic Religious Education in Islamic Higher Education - Surachman, Anista Ika; Kusmawati, Heny (UIR Press, 2025)
The current education system in higher education is shifting to the Outcome Based Education (OBE) approach which emphasizes what graduates can do at the end of the learning experience. Therefore, this study was conducted to produce a product in the form of a descriptive statistics learning module based on OBE for the PAI Study Program. This research is included in research and development (R&D) with the ADDIE model. Analysis by analyzing module requirements, design includes the initial module design, development with module feasibility testing, implementation with module practicality testing, and evaluation through testing the effectiveness of the developed module. The results of the research and development show that the developed module is valid and effective. The results of the comparative pretest and posttest tests show that the significance value of the p-value is 0.000 < 0.05. This means that there is a significant difference between students' abilities before and after using the appropriate descriptive statistics module based on Outcome Based Education (OBE) in learning. The average posttest value (77,74) was greater than the pretest (66,26), indicating that this module is effective for use in learning. The results of this study can be used as a reference for higher education which demands innovation in learning processes and tools that are oriented towards achieving graduate abilities (learning outcomes)